2015
DOI: 10.1007/s11077-015-9227-8
|View full text |Cite
|
Sign up to set email alerts
|

Interest groups in multiple streams: specifying their involvement in the framework

Abstract: Although interests inhabit a central place in the multiple streams framework (MSF), interest groups have played only a minor role in theoretical and empirical studies until now. In Kingdon's original conception, organized interests are a key variable in the politics stream. Revisiting Kingdon's concept with a particular focus on interest groups and their activities-in different streams and at various levels-in the policy process, we take this argument further. In particular, we argue that specifying groups' ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Despite disagreements in five force areas about the existence of a genuine problem that governance transfer could help to address, four of these PCCs were still able to push through their reforms because they occupied powerful political positions. Although it remains useful to analyze problems, policies and politics separately, actors can increase their influence by straddling the different streams (Ackrill and Kay 2011;Rozbicka and Spohr 2016). Our study suggests that if policy entrepreneurs are able to exert influence in each of them, they may find it easier to effect changeparticularly if a focusing event helps to open a window in the problem stream.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite disagreements in five force areas about the existence of a genuine problem that governance transfer could help to address, four of these PCCs were still able to push through their reforms because they occupied powerful political positions. Although it remains useful to analyze problems, policies and politics separately, actors can increase their influence by straddling the different streams (Ackrill and Kay 2011;Rozbicka and Spohr 2016). Our study suggests that if policy entrepreneurs are able to exert influence in each of them, they may find it easier to effect changeparticularly if a focusing event helps to open a window in the problem stream.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, where the MSA has been applied at the subnational level, studies have found that the same actors sometimes operate in different streams. For example, Robinson and Eller (2010) found that actors who participate in one stream are much more likely to be active in others, and Mucciaroni (2013) and Herweg, Zahariadis, and Zohlnhöfer (2018) suggest that participation in different streams may depend on the nature of the problem that the policy solution seeks to address (see also Rozbicka and Spohr 2016;Reardon 2018). Given that recent scholarship has emphasized that policy entrepreneurs sometimes construct problems that their preferred solutions might help to address (Knaggård 2015;Cairney 2018;Petridou and Mintrom 2020) and that these entrepreneurs may also be elected officials who operate in political contextswe can see how their participation is not confined to the policy stream.…”
Section: The Multiple Streams Approachmentioning
confidence: 99%
“…However, most research focuses on the EU institutions themselves: the European Commission is considered to be the main policy entrepreneur due to its right of initiative (Nugent and Rhinard 2019), while in external policy the High Representative of the Union for Foreign Affairs and Security Policy acts as an entrepreneur (Vanhoonacker and Pomorska 2013). There has only been a marginal application of the MSF and the corresponding concept of policy entrepreneur to NGOs in the EU (Rozbicka and Spohr 2016). This is somewhat surprising, as the concept has been applied to other private organisations such as think tanks (Sherrington 2000;Stone 2000).…”
Section: Policy Streams and Entrepreneurshipmentioning
confidence: 99%
“…If we take an example from the theoretical frameworks summarized in the previous section, it is quite clear the Multiple Stream Approach considers interest groups to have a role in all the three streams; however, they are not investigated in a specific way, exactly because in this framework what matters are time, contingencies, and entrepreneurial actions, while interest groups, like other actors, are simply considered as participating in the "normal" dynamics of the three streams. However, it has been suggested that the analytical attention can focus not only on how interest groups are involved in the three streams but also on how they can act as entrepreneurs in agendasetting (Rozbicka & Spohr, 2016).…”
Section: Interest Groups and Public Policy: A Long-lasting And Complementioning
confidence: 99%